2009
DOI: 10.4103/0973-029x.57673
|View full text |Cite
|
Sign up to set email alerts
|

Amelogenesis imperfecta: Report of a case and review of literature

Abstract: Amelogenesis imperfecta (AI) is a diverse collection of inherited diseases that exhibit quantitative or qualitative tooth enamel defects in the absence of systemic manifestations. Also known by varied names such as Hereditary enamel dysplasia, Hereditary brown enamel, Hereditary brown opalescent teeth, this defect is entirely ectodermal, since mesodermal components of the teeth are basically normal. The AI trait can be transmitted by either autosomal dominant, autosomal recessive, or X-linked modes of inherita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 35 publications
1
25
0
3
Order By: Relevance
“…Deviation from this pattern may lead to AI. [36] Mutation or alteration in any of the genes encoding specific enamel proteins such as Enamelin gene (ENAM), Amelogenin gene (AMELX), Kallikrein 4 gene (KLK4), Matrix Metalloproteinase 20 gene (MMP-20), and Distal-less homeobox 3 gene (DLX3) have been linked with AI. [7] Studies showed that AI is familial and can be inherited as autosomal dominant, autosomal recessive, or x-linked dominant and x-linked recessive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deviation from this pattern may lead to AI. [36] Mutation or alteration in any of the genes encoding specific enamel proteins such as Enamelin gene (ENAM), Amelogenin gene (AMELX), Kallikrein 4 gene (KLK4), Matrix Metalloproteinase 20 gene (MMP-20), and Distal-less homeobox 3 gene (DLX3) have been linked with AI. [7] Studies showed that AI is familial and can be inherited as autosomal dominant, autosomal recessive, or x-linked dominant and x-linked recessive.…”
Section: Discussionmentioning
confidence: 99%
“…Restorative aspects in the primary dentition includes giving glass ionomer restorations and stainless steel crowns, in the mixed dentition stainless steel crowns. [1237]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of these cases is related to many factors, including age, damage severity, aesthetics, socioeconomic status, psychosocial aspects, and functional and social demands (14,16,17).…”
Section: Immediate Treatment Of Amelogenesis Imperfectamentioning
confidence: 99%
“…This is entirely ectodermal, since mesodermal component of the teeth are basically normal. Amelogenesis imperfecta trait can be transmitted by either autosomal dominant, autosomal recessive or X-linked mode of inheritance [5]. The other causes of amelogenesis imperfecta include febrile illness or vitamin deficiency, local infection or trauma, fluoride ingestion, congenital syphilis, birth injury, premature birth or idiopathic factors [6].…”
Section: Introductionmentioning
confidence: 99%